Severe acute pancreatitis - Yuan-Yuan HUANG; Pan GONG; Li TIAN (Yixue xinzhi zazhi)
Severe acute pancreatitis is the most dangerous type of acute pancreatitis, often leading to multiple organ failure and systemic inflammatory response syndrome. In recent years, the incidence rate of severe acute pancreatitis has gradually increased, and the mortality rate is high. Early diagnosis and treatment are particularly important for reducing the risk of death in patients with severe acute pancreatitis. This article reviews the latest research progress in the diagnosis and treatment of severe acute pancreatitis in recent years.